2019
DOI: 10.1111/bpa.12699
|View full text |Cite
|
Sign up to set email alerts
|

Brain‐derived and circulating vesicle profiles indicate neurovascular unit dysfunction in early Alzheimer’s disease

Abstract: Vascular factors that reduce blood flow to the brain are involved in apparition and progression of dementia. We hypothesized that cerebral hypoperfusion (CH) might alter the molecular compositions of brain intercellular communication mechanisms while affecting the neurovascular unit in preclinical and clinical human dementias. To test that hypothesis, mice were subjected to bilateral common carotid stenosis (BCAS) and the molecular compositions of brain-derived and circulating extracellular vesicles (EVs) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 77 publications
6
43
0
Order By: Relevance
“…Irrespective, the proteomic data suggest attenuation of coagulation cascade factors and modulation of protective factors such as calmodulin in CAD is possible. Also, we recently reported protein profiles in brain‐derived extracellular vesicles were similarly regulated under conditions of cerebral hypoperfusion in both the human brain and long‐term BCAS mouse brain . Further application of in‐vivo physiological screening, for example, vascular autoregulation, haemodynamic changes as well as assessment of angiogenesis, neurogenesis, neurovascular and gliovascular integrity would enable elucidation of mechanisms associated with effects of EE in long‐term BCAS models.…”
Section: Discussionmentioning
confidence: 97%
“…Irrespective, the proteomic data suggest attenuation of coagulation cascade factors and modulation of protective factors such as calmodulin in CAD is possible. Also, we recently reported protein profiles in brain‐derived extracellular vesicles were similarly regulated under conditions of cerebral hypoperfusion in both the human brain and long‐term BCAS mouse brain . Further application of in‐vivo physiological screening, for example, vascular autoregulation, haemodynamic changes as well as assessment of angiogenesis, neurogenesis, neurovascular and gliovascular integrity would enable elucidation of mechanisms associated with effects of EE in long‐term BCAS models.…”
Section: Discussionmentioning
confidence: 97%
“…These events lead to infiltration of the parenchyma by leukocytes and parenchymal brain damage (Ramirez et al, 2018;Passamonti et al, 2019). Additionally, recent studies have suggested that EVs may be important mediators of AD (Goetzl et al, 2016;Dickhout and Koenen, 2018;Gallart-Palau et al, 2019). Brain-derived and systemic EVs could mediate systemic inflammation as well as brain and NVU dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Since numerous publications have reported tissue-derived EVs without thorough protein characterization of EV-depleted cellular markers and specific EV subtype markers 12,15,16,[49][50][51][52] , we compared the BH and bdEV proteomes with established EV-related databases. Substantial concordance between our data and the databases was clear (Tabe 3).…”
Section: Discussionmentioning
confidence: 99%